Analysis of Basic Factors and Principles of Curriculum Development from the Period of Education in Indonesia - Putri, Sesi Yohana; Khairat, Annisaul (Lembaga Yasin AlSys, 2023)
Curriculum changes in Indonesia from time to time cannot be separated from these factors that affects it is the man himself. Increasingly sophisticated developments causing various changes to aspects of human life, one of which is changes in curriculum development caused by changing human needs along with time. The purpose of this study is to determine the factors and principles the basis for curriculum development from the past in Indonesian education units. This study uses a qualitative method with a library research model. information on This research was obtained from various sources, namely from books, articles and related journals the problems discussed in this study, then analyzed and concluded by the author from references that have been read into an article. The results of this study are in curriculum development there are factors that influence its development includes universities, communities and value systems. While the principles contained in curriculum development, namely the basic principles include the principles of effectiveness, flexibility, continuity, practice and effectiveness and the principles specifically encompassing the principles concerned with educational goals, principles relating to the selection of educational content. Conclusion this research is in curriculum development there are background factors behind its development and in curriculum development there are basic principles and special principles.